1998
DOI: 10.1891/0047-2220.29.3.31
|View full text |Cite
|
Sign up to set email alerts
|

Workplace and Disabilities: Opinions on Work, Interpersonal, and Intrapersonal Factors

Abstract: Designed to provide for the elimination of discrimination against individuals with disabilities, the Americans with Disabilities Act (ADA) more significantly provided for the removal of barriers to their employment. This study ascertained opinions of college students with disabilities regarding work, interpersonal, and intrapersonal factors as concerns to their workplace opportunities and participations. The study found that they have less opportunities than others without disabilities, supervisors are less un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0
1

Year Published

2001
2001
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 0 publications
0
5
0
1
Order By: Relevance
“…The PCA results explained approximately 61% of total variance from the five extracted scales, which represent preoccupations specific to this population in their work integration process. Chima (1998) revealed in his study that the main intrapersonal barriers to employment of people with different kinds of disabilities pertain to selfdoubt concerns (e.g., feeling inadequate, afraid of mistakes). Interestingly, on one hand, lack of self-confidence and lack of assertiveness with coworkers emerge as important barriers to employment for people with mental illness; on the other hand, the first dimension from the Coping Efficacy subscale gathers together items inherent to intrapersonal and interpersonal self-competence/ self-confidence, whereas Chima (1998) differentiated these two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…The PCA results explained approximately 61% of total variance from the five extracted scales, which represent preoccupations specific to this population in their work integration process. Chima (1998) revealed in his study that the main intrapersonal barriers to employment of people with different kinds of disabilities pertain to selfdoubt concerns (e.g., feeling inadequate, afraid of mistakes). Interestingly, on one hand, lack of self-confidence and lack of assertiveness with coworkers emerge as important barriers to employment for people with mental illness; on the other hand, the first dimension from the Coping Efficacy subscale gathers together items inherent to intrapersonal and interpersonal self-competence/ self-confidence, whereas Chima (1998) differentiated these two dimensions.…”
Section: Discussionmentioning
confidence: 99%
“…In other words, the attitudes of consumers, providers of vocational rehabilitation services, and employers have the potential to affect employment outcomes for persons with disabilities. Research concerning the attitudes of three groups-graduate students in rehabilitation counseling, students with disabilities, and small business employers-indicated that employers had the least knowledge of, and poorest attitudes toward, the ADA (Chima, 1998). This study found that university students with disabilities were not confident that the ADA would assure fair employment practices for them.…”
mentioning
confidence: 70%
“…There is some evidence that large employers have increased their hiring of persons with disabilities, whereas small employers have curtailed hiring (Chima, 1998). Employers may make decisions based on stereotypes of disability rather than on actual abilities (Blanck, 1996).…”
Section: Reasons For Discriminationmentioning
confidence: 99%
“…Discrimination against individuals with disabilities still persists, especially in employment; unemployment rates of those with severe disabilities remains at roughly 70% (Ogle, Moses, et al, 1998). College students with disabilities admit a lack of confidence in the ADA's impact and a continued perception that they have fewer employment opportunities than those without disabilities (Chima, 1998).…”
Section: Good Newsmentioning
confidence: 99%